Eyelid Xanthelasma: surgical treatment as the first choice - Marilho Tadeu Dornelas; Nathália Villarins Pedrosa; Gabriel Victor Dornelas; Alfredo Chaoubah; Andrey da Silva Fernandes; Emmanuel de Lima Carvalho; Larissa Vitoria Dornelas; Thaíssa Ramim Reis Belgo (Revista Brasileira de Cirurgia Plástica)
Introduction: Eyelid xanthelasma is the most common form of cutaneous xanthoma, characterized by yellowish patches on the eyelid’s skin. Despite being a benign condition and not presenting with functional limitations, it is an important aesthetic complaint that impacts the patient’s social and emotional life. There are clinical therapeutic options, but the most widespread approach is the surgical approach with excision of the lesions, a simple procedure with few complications and lower local recurrence rates. This study aims to describe the surgical treatment of palpebral xanthelasma, to assess postoperative patient satisfaction and post-surgical recurrence rates. Methods: This is a retrospective study with a sample of 25 patients undergoing surgical treatment of eyelid xanthelasmas. Postoperative follow-up was performed at intervals of 7 days, 30 days, 90 days and 12 months with an interview, physical examination and application of a questionnaire that included the identification of local recurrences, postoperative complications and satisfaction with the aesthetic result. Results: Four patients evolved with local recurrence, and only two expressed dissatisfaction with the aesthetic result after the outcome. No patient who underwent surgical resection of lesions associated with autograft recurrence or dissatisfaction with the aesthetic result was observed. Conclusions: Surgical treatment as the first option in the therapeutic approach of eyelid xanthelasmas should be considered, given the aesthetic and psychological impact of such a condition. It is a simple technique, easy to apply and reproducible, effective, and safe, with relevant satisfaction rates and low recurrences.